2017
DOI: 10.1007/s00299-017-2104-5
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin in plant height control: old player, new story

Abstract: Height relates to plant architecture, lodging resistance, and yield performance. Growth-promoting phytohormones gibberellins (GAs) play a pivotal role in plant height control. Mutations in GA biosynthesis, metabolism, and signaling cascades influence plant height. Moreover, GA interacts with other phytohormones in the modulation of plant height. Here, we first briefly describe the regulation of plant height by altered GA pathway. Then, we depict effects of the crosstalk between GA and other phytohormones on pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(95 citation statements)
references
References 58 publications
1
93
0
1
Order By: Relevance
“…Moreover, the variations that happened in upstream regions of 12 candidate genes with 29 haplotypes were selected for further verifying (Figure ). As we know, the hormones, including gibberellin (GA), auxin (IAA), brassinosteroids (BRs) and cytokinin (CK), have mainly taken part in the process of the division or elongation of cells and played a significant role in controlling the PH of plants (Ubeda‐Tomas & Bennett, ; Wang, Zhao, Lu, & Deng, ). Therefore, six of the 12 genes containing the motifs like TATC‐box, TGA‐element and AuxRE ( Glym a.01G023100, TATC‐box; Glyma.03G207700 , TGA‐element; Glyma.12G182500 , TGA‐element; Glyma.16G137500 , TGA‐element; Glyma.20G122200 , TATC‐box and AuxRE; Glyma .20G122300, AuxRE) which were involved in gibberellin or auxin responsiveness were selected and identified with qRT‐PCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the variations that happened in upstream regions of 12 candidate genes with 29 haplotypes were selected for further verifying (Figure ). As we know, the hormones, including gibberellin (GA), auxin (IAA), brassinosteroids (BRs) and cytokinin (CK), have mainly taken part in the process of the division or elongation of cells and played a significant role in controlling the PH of plants (Ubeda‐Tomas & Bennett, ; Wang, Zhao, Lu, & Deng, ). Therefore, six of the 12 genes containing the motifs like TATC‐box, TGA‐element and AuxRE ( Glym a.01G023100, TATC‐box; Glyma.03G207700 , TGA‐element; Glyma.12G182500 , TGA‐element; Glyma.16G137500 , TGA‐element; Glyma.20G122200 , TATC‐box and AuxRE; Glyma .20G122300, AuxRE) which were involved in gibberellin or auxin responsiveness were selected and identified with qRT‐PCR.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, a total of 134 potential candidate genes were identified in 200‐kb genomic regions among the 14 association signals. Some genes associated with cell division or elongation, plant hormone metabolisms, proteins modification or degradation and signalling or transport of specific proteins, have been found to participate in the regulation of PH in soybean (Jung et al, ; Ubeda‐Tomas & Bennett, ; Wang, Zhao, et al, ; Yao et al, ; Zhong et al, ). To further identify the candidate genes that regulated PH, haplotype analysis of candidate genes was conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At beginning of the flowering stage, the average plant height among 8 treatments was 46.50 cm, in which the maximum was observed in F8 (51.28 cm), followed by F5 (51.03 cm), F6 (50.16 cm), and F2 (49.75 cm). In these formulas, supplementary GA 3 was applied, and it was one of the major factors that contributed to the development of plant height [16]. Additionally, micronutrient fertilizer and Ca(NO 3 ) 2 foliar fertilizer were also applied in F8, leading to the highest plant height value found in this formula.…”
Section: Resultsmentioning
confidence: 99%
“…very large numbers of small additive effect loci) with some large effect loci likely fixed during domestication and early selection [23]. Functional genetic variation in terminal plant height has been shown to be controlled through hormones; mutations within the (i) gibberellin biosynthesis pathways [33] and crosstalk with other phytohormomes including: (ii) auxin [34] and (iii) brassinosteriods [3538]. Hormones are well known to fluctuate throughout plant growth, responding to environmental and developmental stimuli [3942].…”
Section: Introductionmentioning
confidence: 99%